Creating Better Innovation Measurement Practices - Richtnér, Anders; Brattström, Anna; Frishammar, Johan; Björk, Jennie; Magnusson, Mats; O'Reilly, Tim; Rometty, Ginni; Davenport, Thomas; Moore, Andrew; Hoffman, Reid; Agrawal, Ajay; Gans, Joshua; et al. (MIT Sloan Management Review, 2017)
At most companies, innovation is a top managerial priority. Many managers look at successful innovators such as Apple Inc. and Google Inc. with envy, wishing that their companies could be half as innovative. To boost and benchmark innovation, managers often use quantitative performance indicators. Some measure innovation as results or outcomes, such as sales from new products; others measure innovation as a process, using metrics such as the number of innovation projects; some rely on input metrics; and still others focus on the innovation portfolio by looking at factors such as the percentage of investments in breakthrough projects versus line extensions. The key managerial challenge, the authors argue, does not lie in identifying metrics; there is no shortage to choose from. Rather, they say, it is understanding the problem that measurement should solve for the company and, based on that insight, designing and implementing a useful innovation measurement framework that is appropriate to the organization's needs. To do this, managers need to understand the innovation challenges the company faces, how innovation is currently measured, and the extent to which current measurement practices help or hinder efforts to achieve innovation goals. Only then will they be able to steer clear of common innovation measurement mistakes, such as placing too much value on data at the expense of meaning, or getting bogged down with too many measures that provide contradictory advice and incentivize employees to do the wrong things. The article contains a step-by-step framework that allows managers to identify whether their current innovation measurement practices need to change and, if so, how to go about measuring innovation more effectively. The framework is also aimed at companies that do not currently measure innovation but would like to start. The authors build their framework around three phases designed to help companies improve their innovation management practices: (A) assess current innovation measurement practices, (B) improve core innovation measurement practices, and (C) deploy the improved innovation measurement practices. Each phase involves distinct steps that companies should take. The authors write that their framework "is designed to help both individual executives and companies take control of their innovation measurement and understand the critical decisions, traps, and trade-offs involved - thereby allowing organizations to realize t ...